Preparation method of high-strength ceramic fiber material
By modifying and photoinduced crosslinking in ceramic fiber materials, the problem of poor mechanical properties of ceramic fiber materials is solved, and the preparation of high-strength and good thermal conductivity is realized.
Patent Information
- Application Number
- CN202411592580.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-02-18
AI Technical Summary
Ceramic fiber materials have poor mechanical properties and are prone to fragmentation under external forces, affecting the thermal insulation effect.
A high-strength ceramic fiber material is formed by mixing the modified aluminum silicate ceramic fibers and modified polyethylene glycol in an aluminum acetate solution and crosslinking under near-infrared light.
The mechanical properties of ceramic fiber materials are significantly enhanced, their strength and tensile properties are improved, while maintaining good thermal conductivity.
Smart Images

Figure BDA0005125967550000071 
Figure BDA0005125967550000081
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ceramic materials, and in particular relates to a method for preparing a high-strength ceramic fiber material. Background Art
[0002] Ceramic fiber is a fibrous lightweight refractory material with the advantages of light weight, high temperature resistance, good thermal stability, low thermal conductivity, low specific heat and resistance to mechanical vibration. Materials made of ceramic fiber have good fireproofing and thermal insulation properties. Ceramic fiber thermal insulation materials can be used in many high-temperature occasions because they have the performance characteristics of high temperature resistance and low thermal conductivity. They can effectively block the heat from the surface of thermal insulation structures or ultra-high temperature components to other components. However, in the actual construction process, the mechanical properties of ceramic fiber thermal insulation materials are poor, and they are very easy to break under the action of external forces, which increases the difficulty of construction. In addition, the appearance of cracks will directly affect the thermal insulation effect of the material.
[0003] The patent application with publication number CN109534779 A discloses a high-strength ceramic fiber thermal insulation material and a preparation method thereof, the method comprising: placing ceramic fibers in an acetate solution, mixing evenly, loading the mixed slurry into a metal clamping plate mold, applying pressure, placing in an oven, raising the oven temperature, naturally cooling to room temperature after heat preservation and pressure maintenance, drying, and cooling to obtain the ceramic fiber thermal insulation material. The application process is simple, with low preparation cost, short reaction time, low energy consumption, and high production efficiency, but there is a problem of low mechanical strength.
[0004] In order to overcome the problem of poor mechanical properties of ceramic fiber materials, the current solution is to add a certain amount of adhesive, such as aluminum phosphate adhesive, chromium phosphate adhesive, aluminum silicate adhesive, aluminum sol, etc., when preparing ceramic fiber materials. However, the addition of adhesive will increase the thermal conductivity of the material and significantly increase the weight of the fiber insulation material, which is very unfavorable for the assembly of devices with load requirements. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing a high-strength ceramic fiber material to solve the problem of poor mechanical properties of the ceramic fiber material.
[0006] The purpose of the present invention can be achieved through the following technical solutions:
[0007] A method for preparing a high-strength ceramic fiber material comprises the following steps:
[0008] 1) placing the modified aluminum silicate ceramic fiber, modified polyethylene glycol and a photoinitiator into an aluminum acetate solution with a concentration of 28 wt%, mixing them evenly, and irradiating them with near-infrared light to obtain a modified ceramic fiber material;
[0009] 2) The modified ceramic fiber material is placed in a mold and fixed therein and then pressurized; after heating and drying, the mold is naturally cooled to obtain a high-strength ceramic fiber material.
[0010] Furthermore, the dosage ratio of the modified aluminum silicate ceramic fiber, modified polyethylene glycol, photoinitiator and aluminum acetate is 40-45 mg: 450-500 mg: 10-15 mg: 25-30 mL; and the photoinitiator is lithium phenyl-2,4,6-trimethylbenzoylphosphinate.
[0011] Furthermore, the near-infrared light irradiation is 380-400 nm, and the irradiation time is 1-3 min.
[0012] Furthermore, the pressurization pressure ranges from 6 to 8 MPa; and the heating temperature ranges from 155 to 165°C.
[0013] Furthermore, the modified aluminum silicate ceramic fiber is prepared by the following steps:
[0014] The silane coupling agent containing methyl acrylate is dissolved in deionized water and the pH is adjusted to obtain a coupling agent hydrolyzate; aluminum silicate is placed in an ethanol / water mixture and ultrasonically dispersed to obtain an aluminum silicate dispersion; the coupling agent hydrolyzate is added to the aluminum silicate dispersion, heated and stirred at 70-80° C. for 6-8 hours, centrifuged and washed, and dried to obtain modified aluminum silicate ceramic fibers.
[0015] Furthermore, the dosage ratio of the methacrylate-containing silane coupling agent, deionized water, aluminum silicate and ethanol / water mixture is 0.15-0.2 g: 5-7 mL: 5-7 g: 180-200 mL; the mass ratio of ethanol / water is 1:1; and the pH is adjusted to 3-4.
[0016] Furthermore, the methacrylate-containing silane coupling agent is one of KH-570, G-570 and γ-methacrylateoxypropyltriethoxysilane.
[0017] Further, the modified polyethylene glycol is prepared by the following steps:
[0018] Dissolve polyethylene glycol, 4-dimethylaminopyridine and trifluoromethylpyridine in CH2Cl2 solution, stir at room temperature to obtain solution A; slowly add triethylamine and CH2Cl2 solution of 4-nitrophenyl chloroformate to solution A, stir for 5 to 6 hours; obtain solution B; evaporate in a vacuum at 40°C for 5 to 6 minutes; pour solution B into ether, collect the precipitate to obtain precipitate C; place precipitate C, triethylamine, N-(2-aminoethyl)-4-[4-(hydroxymethyl)-2-methoxy-5-nitrophenoxy]-butyramide in DMF, stir at room temperature for 6 to 8 hours, remove the solvent, wash and freeze-dry to obtain modified polyethylene glycol.
[0019] Furthermore, the usage ratio of the polyethylene glycol, 4-dimethylaminopyridine, trifluoromethylpyridine, triethylamine and 4-nitrophenyl chloroformate is 9-10 g: 0.005-0.01 g: 0.005-0.01 g: 0.1-0.15 g: 0.2-0.25 g;
[0020] Furthermore, the usage ratio of the precipitate C, triethylamine, N-(2-aminoethyl)-4-[4-(hydroxymethyl)-2-methoxy-5-nitrophenoxy]-butyramide and DMF is 8-9 g: 0.1-0.15 g: 0.4-0.5 g: 50-60 mL.
[0021] Beneficial effects of the present invention:
[0022] (1) The ceramic fiber material prepared by the present invention takes aluminum silicate ceramic fiber as the matrix. The aluminum silicate ceramic fiber is modified by a coupling agent, and then the modified polyethylene glycol is introduced. Under the guidance of a photoinitiator, the two are cross-linked, and the groups on the modified polyethylene glycol are photolyzed to produce nitroso groups, which are covalently bonded with the carbon center groups on the modified aluminum silicate ceramic fiber, thereby greatly enhancing the mechanical properties of the material.
[0023] (2) The aluminum acetate solution used in the present invention has good solubility for aluminum silicate. At the same time, aluminum acetate has a low decomposition temperature. It decomposes into oxides at a relatively low temperature and deposits in the cross-linked pores and connection points, thereby improving the strength of the material. Polyethylene glycol, as a good dispersant, improves the dispersibility of the oxides. On the other hand, the preparation method of the present invention has a relatively low temperature, thereby avoiding the decomposition of polyethylene glycol at high temperatures. DETAILED DESCRIPTION
[0024] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0025] Example 1
[0026] This embodiment provides a high-strength ceramic fiber material, which is prepared by the following steps:
[0027] 1) Dissolve 0.2 g KH-570 in 6 mL deionized water and adjust the pH to 3 to obtain a coupling agent hydrolyzate; place 6 g aluminum silicate in 200 mL of an ethanol / water mixture with a mass ratio of 1:1, and disperse by ultrasonic to obtain an aluminum silicate dispersion; add the coupling agent hydrolyzate to the aluminum silicate dispersion, heat and stir at 70° C. for 6 h, centrifuge and wash, and dry to obtain a modified aluminum silicate ceramic fiber;
[0028] Dissolve 8 g of polyethylene glycol, 0.005 g of 4-dimethylaminopyridine and 0.005 g of trifluoromethylpyridine in 100 mL of CH2Cl2 solution, stir at room temperature to obtain solution A; slowly add 3 mL of CH2Cl2 solution of 0.1 g of triethylamine and 0.2 g of 4-nitrophenyl chloroformate to solution A, and stir for 6 h to obtain solution B; evaporate in a vacuum at 40°C for 6 min; pour solution B into ether, collect the precipitate to obtain precipitate C; place 8 g of precipitate C, 0.1 mL of triethylamine and 0.4 g of N-(2-aminoethyl)-4-[4-(hydroxymethyl)-2-methoxy-5-nitrophenoxy]-butyramide in 50 mL of DMF, stir at room temperature for 8 h, remove the solvent, wash and freeze-dry to obtain modified polyethylene glycol.
[0029] 45 mg of modified aluminum silicate ceramic fiber, 500 mg of modified polyethylene glycol and 15 mg of phenyl-2,4,6-trimethylbenzoyl phosphinate lithium were placed in 30 mL of 28 wt% aluminum acetate solution, mixed evenly, and irradiated with 400 nm near-infrared light for 2 min to obtain a modified ceramic fiber material;
[0030] 2) The modified ceramic fiber material is placed in a mold and fixed, and a pressure of 8 MPa is applied; the mold is heated and dried at 160° C., and then naturally cooled to obtain a high-strength ceramic fiber material.
[0031] Example 2
[0032] The present embodiment is different from the embodiment 1 in that the irradiation time of 2 minutes in 1) is changed to irradiation time of 1 minute.
[0033] The remaining raw materials and preparation process remain the same as in Example 1.
[0034] Example 3
[0035] The present embodiment differs from the embodiment 1 in that "applying a pressure of 8 MPa" in 2) is changed to "applying a pressure of 6 MPa".
[0036] The remaining raw materials and preparation process remain the same as in Example 1.
[0037] Example 4
[0038] The present embodiment differs from the embodiment 1 in that the “0.2 g KH-570, 6 g aluminum silicate” in 1) is changed to “0.15 g KH-570, 7 g aluminum silicate”.
[0039] The remaining raw materials and preparation process remain the same as in Example 1.
[0040] Example 5
[0041] The difference between this embodiment and embodiment 1 is that "0.2 g KH-570" in 1) is changed to "0.2 g G-570".
[0042] The remaining raw materials and preparation process remain the same as in Example 1.
[0043] Example 6
[0044] The difference between this embodiment and embodiment 1 is that "adjusting the pH to 3" in 1) is changed to "adjusting the pH to 4".
[0045] The remaining raw materials and preparation process remain the same as in Example 1.
[0046] Comparative Example 1
[0047] Compared with Example 1, this comparative example differs in that the polyethylene glycol is not modified in 1), and the specific implementation steps are as follows:
[0048] 1) Dissolve 0.2 g KH-570 in 6 mL deionized water and adjust the pH to 3 to obtain a coupling agent hydrolyzate; place 6 g aluminum silicate in 200 mL of an ethanol / water mixture with a mass ratio of 1:1, and disperse by ultrasonic to obtain an aluminum silicate dispersion; add the coupling agent hydrolyzate to the aluminum silicate dispersion, heat and stir at 70° C. for 6 h, centrifuge and wash, and dry to obtain a modified aluminum silicate ceramic fiber;
[0049] 45 mg of modified aluminum silicate ceramic fiber, 500 mg of polyethylene glycol and 15 mg of phenyl-2,4,6-trimethylbenzoyl phosphinate lithium were placed in 30 mL of 28 wt% aluminum acetate solution, mixed evenly, and irradiated with 400 nm near-infrared light for 2 min to obtain a modified ceramic fiber material;
[0050] 2) The modified ceramic fiber material is placed in a mold and fixed, and a pressure of 8 MPa is applied; the mold is heated and dried at 160° C., and then naturally cooled to obtain a high-strength ceramic fiber material.
[0051] Comparative Example 2
[0052] Compared with Example 1, this comparative example differs in that, in 1), aluminum silicate is not modified, and the specific implementation steps are as follows:
[0053] 1) Dissolve 8 g of polyethylene glycol, 0.005 g of 4-dimethylaminopyridine and 0.005 g of trifluoromethylpyridine in 100 mL of CH2Cl2 solution and stir at room temperature to obtain solution A; slowly drop 3 mL of CH2Cl2 solution of 0.1 g of triethylamine and 0.2 g of 4-nitrophenyl chloroformate into solution A and stir for 6 h to obtain solution B; evaporate in vacuo at 40°C for 6 min; pour solution B into ether and collect the precipitate to obtain precipitate C; place 8 g of precipitate C, 0.1 mL of triethylamine and 0.4 g of N-(2-aminoethyl)-4-[4-(hydroxymethyl)-2-methoxy-5-nitrophenoxy]-butyramide in 50 mL of DMF and stir at room temperature for 8 h. Remove the solvent, wash and freeze-dry to obtain modified polyethylene glycol.
[0054] 45 mg of aluminum silicate, 500 mg of modified polyethylene glycol and 15 mg of phenyl-2,4,6-trimethylbenzoyl phosphinate lithium were placed in 30 mL of 28 wt% aluminum acetate solution, mixed evenly, and irradiated with 400 nm near-infrared light for 2 min to obtain a modified ceramic fiber material;
[0055] 2) The modified ceramic fiber material is placed in a mold and fixed, and a pressure of 8 MPa is applied; the mold is heated and dried at 160° C., and then naturally cooled to obtain a high-strength ceramic fiber material.
[0056] Comparative Example 3
[0057] Compared with Example 1, the difference between this comparative example is that in 1), aluminum silicate and polyethylene glycol are not modified at the same time, and the specific implementation steps are as follows:
[0058] 1) 45 mg of aluminum silicate, 500 mg of polyethylene glycol and 15 mg of phenyl-2,4,6-trimethylbenzoyl phosphinate lithium were placed in 30 mL of 28 wt% aluminum acetate solution, mixed evenly, and irradiated with 400 nm near-infrared light for 2 min to obtain a modified ceramic fiber material;
[0059] 2) The modified ceramic fiber material is placed in a mold and fixed, and a pressure of 8 MPa is applied; the mold is heated and dried at 160° C., and then naturally cooled to obtain a high-strength ceramic fiber material.
[0060] Comparative Example 4
[0061] The difference between this comparative example and Example 1 is that the "30 mL of 28 wt % aluminum acetate solution" in 1) is changed to "30 mL of deionized water".
[0062] The remaining raw materials and preparation process remain the same as in Example 1.
[0063] Comparative Example 5
[0064] The difference between this comparative example and Example 1 is that in 1), "400 nm near-infrared light irradiation" is changed to "visible light irradiation".
[0065] The remaining raw materials and preparation process remain the same as in Example 1.
[0066] Comparative Example 6
[0067] The difference between this comparative example and Example 1 is that in 1), "irradiation with 400 nm near-infrared light" is changed to "placed in dark conditions".
[0068] The remaining raw materials and preparation process remain the same as in Example 1.
[0069] Comparative Example 7
[0070] The difference between this comparative example and Example 1 is that "heating at 160°C" in 2) is changed to "heating to 400°C"
[0071] The remaining raw materials and preparation process remain the same as in Example 1.
[0072] The compressive strength (KPa), tensile strength (KPa) and thermal conductivity (W / m*K) of Examples 1 to 6 and Comparative Examples 1 to 7 were tested;
[0073] The results are shown in Table 1:
[0074] Table 1
[0075]
[0076]
[0077] It can be seen from Table 1 that, compared with Example 1, Example 2 and Comparative Examples 5 to 6 mainly explore the effects of illumination time, illumination type and whether illumination is present on the material. The results show that after replacing near-infrared light with visible light, the cross-linking effect between the components disappears, resulting in a significant decrease in the final mechanical strength. Without illumination, the mechanical properties exhibited are even worse. Compared with Example 1, Examples 3 and 4 to 6 adjust the experimental raw materials and conditions within a reasonable range, and ceramic fiber materials with high strength and good thermal conductivity can be obtained.
[0078] Comparing Comparative Examples 1 to 3 with Example 1, the strength of the materials prepared by Comparative Examples 1 and 2 decreased to varying degrees, and the decrease in Comparative Example 3 was even greater, indicating the necessity of modification of polyethylene glycol and aluminum silicate for photoinduced crosslinking; Compared with Example 1, the strength of the ceramic fiber decreased after the solvent was replaced with water in Comparative Example 4, because aluminum acetate decomposed into oxides and deposited in the cross-linked pores and connection points to improve the strength of the material; Comparative Examples 3, 5 to 6 were compared with each other and found that when aluminum silicate and polyethylene glycol were not modified, the results were similar to those without near-infrared light irradiation, proving that near-infrared light irradiation and modification of components are indispensable for improving the mechanical properties of the material; Compared with Example 1, Comparative Example 7 is mainly reflected in the effect of heating temperature on the material. The results show that excessively high temperature will cause polyethylene glycol to decompose, which will cause the oxides decomposed from aluminum acetate to be unevenly dispersed, and ultimately cause the mechanical properties of the ceramic fiber material to decrease; At a suitable temperature, the modified polyethylene glycol cross-links with the modified aluminum silicate ceramic fiber under the guidance of the photoinitiator to improve the strength of the material.
[0079] In summary, the present invention provides a method for preparing a high-strength ceramic fiber material. The prepared ceramic fiber material has high strength, good thermal conductivity, and good application prospects.
[0080] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0081] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a high-strength ceramic fiber material, characterized in that: The steps include: 1) placing the modified aluminum silicate ceramic fiber, modified polyethylene glycol and a photoinitiator into an aluminum acetate solution with a concentration of 28 wt%, mixing them evenly, and irradiating them with near-infrared light to obtain a modified ceramic fiber material; 2) placing the modified ceramic fiber material in a mold and fixing it under pressure; After heating and drying and then naturally cooling, a high-strength ceramic fiber material is obtained.
2. The method for preparing a high-strength ceramic fiber material according to claim 1, characterized in that: The dosage ratio of the modified aluminum silicate ceramic fiber, the modified polyethylene glycol, the photoinitiator and the aluminum acetate is 40-45 mg: 450-500 mg: 10-15 mg: 25-30 mL; the photoinitiator is lithium phenyl-2,4,6-trimethylbenzoyl phosphinate.
3. The method for preparing a high-strength ceramic fiber material according to claim 1, characterized in that: The near infrared light irradiation is 380-400nm, and the irradiation time is 1-3min.
4. The method for preparing a high-strength ceramic fiber material according to claim 1, characterized in that: The pressurization pressure ranges from 6 to 8 MPa; the heating temperature ranges from 155 to 165°C.
5. The method for preparing a high-strength ceramic fiber material according to claim 1, characterized in that: The modified aluminum silicate ceramic fiber is prepared by the following steps: The silane coupling agent containing methyl acrylate is dissolved in deionized water and the pH is adjusted to obtain a coupling agent hydrolyzate; aluminum silicate is placed in an ethanol / water mixture and ultrasonically dispersed to obtain an aluminum silicate dispersion; the coupling agent hydrolyzate is added to the aluminum silicate dispersion, heated and stirred at 70-80° C. for 6-8 hours, centrifuged and washed, and dried to obtain modified aluminum silicate ceramic fibers.
6. The method for preparing a high-strength ceramic fiber material according to claim 5, characterized in that: The dosage ratio of the methacrylate-containing silane coupling agent, deionized water, aluminum silicate and ethanol / water mixture is 0.15-0.2 g: 5-7 mL: 5-7 g: 180-200 mL; the mass ratio of ethanol / water is 1:1; and the pH is adjusted to 3-4.
7. The method for preparing a high-strength ceramic fiber material according to claim 5, characterized in that: The methacrylate-containing silane coupling agent is one of KH-570, G-570 and γ-methacrylate oxypropyl triethoxy silane.
8. The method for preparing a high-strength ceramic fiber material according to claim 1, characterized in that: The modified polyethylene glycol is prepared by the following steps: Dissolve polyethylene glycol, 4-dimethylaminopyridine and trifluoromethylpyridine in CH2Cl2 solution, stir at room temperature to obtain solution A; slowly add triethylamine and CH2Cl2 solution of 4-nitrophenyl chloroformate to solution A, stir for 5 to 6 hours; obtain solution B; evaporate in a vacuum at 40°C for 5 to 6 minutes; pour solution B into ether, collect the precipitate to obtain precipitate C; place precipitate C, triethylamine, N-(2-aminoethyl)-4-[4-(hydroxymethyl)-2-methoxy-5-nitrophenoxy]-butyramide in DMF, stir at room temperature for 6 to 8 hours, remove the solvent, wash and freeze-dry to obtain modified polyethylene glycol.
9. The method for preparing a high-strength ceramic fiber material according to claim 8, characterized in that: The usage ratio of the polyethylene glycol, 4-dimethylaminopyridine, trifluoromethylpyridine, triethylamine and 4-nitrophenyl chloroformate is 9-10g: 0.005-0.01g: 0.005-0.01g: 0.1-0.15g: 0.2-0.25g.
10. The method for preparing a high-strength ceramic fiber material according to claim 8, characterized in that: The usage ratio of the precipitate C, triethylamine, N-(2-aminoethyl)-4-[4-(hydroxymethyl)-2-methoxy-5-nitrophenoxy]-butyramide and DMF is 8-9 g: 0.1-0.15 g: 0.4-0.5 g: 50-60 mL.
Citation Information
Patent Citations
High-strength ceramic fiber thermal insulation material and preparation method thereof
CN109534779A